2013
DOI: 10.1093/pcp/pct160
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellin-Induced Expression of Fe Uptake-Related Genes in Arabidopsis

Abstract: In dicots, iron (Fe) is acquired from the soil by IRT1 (IRON-REGULATED TRANSPORTER 1) and FRO2 (FERRIC REDUCTION OXIDASE 2) that are localized at the root epidermis. IRT1 and FRO2 expression is induced by local and systemic signals under Fe-deficient conditions in Arabidopsis thaliana. In this study, the expression of IRT1, FRO2, bHLH038 and bHLH39 (the latter two of which control IRT1 and FRO2 expression) was promoted by GA4 treatment of gibberellin (GA) deficient ga3ox1 ga3ox2 mutants. In contrast, the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 63 publications
3
24
0
Order By: Relevance
“…duction of IRT1 and FRO2 expression, whereas GAs enhance their induction by overcoming DELLA-mediated repression. This observation is consistent with a previous work showing that application of exogenous GAs to GA-deficient mutants enhanced the expression of iron-related genes (Matsuoka et al, 2014). It is noteworthy that among these iron-related genes are found bHLH38 and bHLH39, ensuring a feedforward regulation in response to iron deficiency ( Figure S3; Matsuoka et al, 2014).…”
Section: Ga Signaling Modulates Iron Uptakesupporting
confidence: 93%
See 1 more Smart Citation
“…duction of IRT1 and FRO2 expression, whereas GAs enhance their induction by overcoming DELLA-mediated repression. This observation is consistent with a previous work showing that application of exogenous GAs to GA-deficient mutants enhanced the expression of iron-related genes (Matsuoka et al, 2014). It is noteworthy that among these iron-related genes are found bHLH38 and bHLH39, ensuring a feedforward regulation in response to iron deficiency ( Figure S3; Matsuoka et al, 2014).…”
Section: Ga Signaling Modulates Iron Uptakesupporting
confidence: 93%
“…For example, phosphate (Pi) starvation causes a reduction in GA levels, which in turn activates several adaptively significant plant Pi-deficiency responses, such as reduced primary root length and increased lateral root number (Jiang et al, 2007). More recently, exogenously applied GAs have been shown to induce the expression of several iron-uptake-related genes including IRT1 and FRO2, although the mechanism and the role of GA in iron-deficiency responses remain largely unknown (Matsuoka et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, auxin might affect Fe-deficiency responses through more than one pathway, particularly given that it has been shown to exert such diverse effects as modulating lateral root development [76] and post-transcriptionally affecting AHA2 [82]. Quantitative reverse transcription PCR analysis of GA-deficient mutants has shown that GA positively regulates the abundance of BHLH038, BHLH039, FRO2, and IRT1 transcripts; however, FIT was not induced by the application of GA [67]. It is unclear whether GA affects Fe-deficiency responses directly or through the other positive regulators.…”
Section: Protein Network Regulating Fe-dependent Transcriptionmentioning
confidence: 99%
“…This apparent discrepancy might indicate organ-specific effects in IRT1 gene regulation. However, inhibition of gibberellin (GA) biosynthesis leads to a decrease in IRT1 mRNA abundance as expected from the role of GA in promoting Fe uptake [67]. Analysis of different Arabidopsis ecotypes has revealed natural variation in the regulation of IRT1 gene expression.…”
Section: Protein Network Regulating Fe-dependent Transcriptionmentioning
confidence: 99%
“…Gibberellins (GAs) are a classical type of phytohormone that functions in the regulation of various aspects of physiological processes [82]. In arabidopsis, GA signaling is found to be involved in Fe deficiency responses by positively modulating the expression of the Fe-uptake gene [83]. However, there is limited information available on the involvement of GAs in the regulation of Fe homeostasis in rice.…”
Section: Gibberellins (Gas)mentioning
confidence: 99%